2022
DOI: 10.18203/2349-3291.ijcp20220378
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk index of babies-II versus score for neonatal acute physiology-II in predicting mortality and morbidity in preterm babies

Abstract: Background: The measurement of severity of illness using scoring systems is an important aspect in predicting mortality and morbidity in intensive care units which in turn can help in optimizing the limited healthcare resources in developing countries. The primary objective was to determine the correlation between clinical risk index of babies-II (CRIB-II) and score for neonatal acute physiology-II (SNAP-II) scores while the secondary objective was to identify which among them is superior in predicting mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Similar to our study, ROC analysis showed that birth weight and gestational age were not good in the prediction of death when compared to CRIB II. CRIB II (AUC=0.556) demonstrated stronger discrimination than SNAP-II (AUC=0.404) when the two scores were compared to see which one better predicts the overall newborn morbidity, demonstrating that CRIB II was superior to SNAP-PE II overall [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our study, ROC analysis showed that birth weight and gestational age were not good in the prediction of death when compared to CRIB II. CRIB II (AUC=0.556) demonstrated stronger discrimination than SNAP-II (AUC=0.404) when the two scores were compared to see which one better predicts the overall newborn morbidity, demonstrating that CRIB II was superior to SNAP-PE II overall [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, ROC analysis showed that birth weight and gestational age were not good in the prediction of death when compared to CRIB II. CRIB II (AUC=0.556) demonstrated stronger discrimination than SNAP-II (AUC=0.404) when the two scores were compared to see which one better predicts the overall newborn morbidity, demonstrating that CRIB II was superior to SNAP-PE II overall[13].Eighty low-birth-weight newborns were examined in a study by Stomnaroska and Danilovski. Maternal comorbidities and gestational age were substantially linked with neonatal mortality, but not with birth weight.…”
mentioning
confidence: 99%